Penilaian objektif dan hasil program Pendidikan Berasaskan Hasil (OBE): soal selidik majikan industri dan alumni - Shahrir Abdullah,; Norhamidi Muhamad,; Riza Atiq Abdullah O.K. Rahmat,; Baba Md. Deros,; Noorhisham Tan Kofli,; Mardina Abdullah,; Mazlan Mohd. Tahir,; Andanastuti Muchtar, (Penerbit Universiti Kebangsaan Malaysia, 2009)
The teaching concept based on Outcome Based Education (OBE) has been implemented at the Faculty of Engineering, UKM beginning in 2005.Through this approach, each programme is required todevelop programme educational objectives and programme outcomes upon consultation with stakeholders such as government, employers and alumni. Hence, this paper presents a method which can be used to measure stakeholders’ perception on importance and achievement of statements of the programme educational objectives (PEO) and programme outcomes (PO) for engineering programmes offered. In this method, for each statement, attributes that form the statements were identiÞed and would be evaluated based on the 1-5 Likert scale. The questionnaire were sent to industry and alumni based on the Industrial Training and Alumni database of the Faculty of Engineering, and the questions asked are related to signiÞcance level of the statement and the achievement of the graduates and alumni. The result of the survey found that there are indeed several components in the existing PEO and PO statements are not well accepted by many stakeholders, whereas other statements are accepted. Based on this result, the statement can be improved in order to meet the stakeholders, expectation